Nota sobre Odisea 1.7 - Conti, Luz (Exemplaria Classica, 2010)
The genitive α?τ?ν with which the seventh line of the Odyssey starts in the vulgata and in all modern editions allows in principle several interpretations. In this paper, we defend a hypothesis that has so far never been raised: the function of the genitive as the expression of a semi-subject, that is, of a subject that has semantic and pragmatic properties which do not correspond exactly to the properties of the prototypical subject and with a grammatical codification that is also different from the grammatical codification of the prototypical subject, this is, the nominative. This analysis of α?τ?ν solves the disadvantages of other interpretations and is supported by the use of the genitive in other Homeric passages and in the works of subsequent writers. If we accept the hypothesis that is defended in this paper, we would be facing the first example in Greek of unequivocal agreement in number and person between the genitive and its verbal predicate.